1981
DOI: 10.1111/j.1432-1033.1981.tb06332.x
|View full text |Cite
|
Sign up to set email alerts
|

Binding of Spermine to tRNATyr Stabilizes the Conformation of the Anticodon Loop and Creates Strong Binding Sites for Divalent Cations

Abstract: Electron spin resonance (ESR) spectra of yeast tRNATyr, spin‐labelled in the isopentenyladenosine residue adjacent to the anticodon, were measured as a function of temperature at various spermine/tRNA ratios. The critical temperature, at which a change in the activation energy for spin‐label motion takes place, changes abruptly by almost 10°C upon the addition of the fifth spermine molecule/tRNATyr molecule, indicating a marked stabilization of the anticodon region. Scatchard plots for Mn2+ binding to tRNATyr … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

1982
1982
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…This finding supports the notion that the above analogues cannot cause displacement of Mg 2ϩ from the ribosomal class (II) sites suggested by Weiss et al [36]. Also, an hypothetical displacement of Mg 2ϩ from AcPhe-tRNA sites does not seem possible, since Nothig-Laslo et al [42] have found that the parent compound, spermine, does not compete with divalent cations for common binding sites on tRNA.…”
Section: Discussionsupporting
confidence: 86%
“…This finding supports the notion that the above analogues cannot cause displacement of Mg 2ϩ from the ribosomal class (II) sites suggested by Weiss et al [36]. Also, an hypothetical displacement of Mg 2ϩ from AcPhe-tRNA sites does not seem possible, since Nothig-Laslo et al [42] have found that the parent compound, spermine, does not compete with divalent cations for common binding sites on tRNA.…”
Section: Discussionsupporting
confidence: 86%
“…Other mechanisms of protein induction are also possible to be influenced by polyamines. Anticodon loop configuration of tRNA TM is claimed to be stabilized by the binding of spermidine [22]. DNA synthesis by type C reteroviral DNA polymerase was augmented 10 times by 0.5 mM spermine or by 2 mM spermidine [23].…”
Section: Discussionmentioning
confidence: 99%
“…There have been a number of studies on the effects of polyamines on various steps in protein synthesis in vitro, including initiation (19,20) and translation (21), on tRNA structure (22)(23)(24)(25), on tRNA aminoacylation (26), and on the fidelity of translation (27)(28)(29). (For additional references see the articles cited in refs.…”
Section: Discussionmentioning
confidence: 99%